The Supreme Court's decision in Unwired Planet – what comes next?. Issue 4 (January 2021) - Jones, Rachel
Abstract : The Supreme Court's decision in two appeals relating to telecommunications licensing disputes and 'Standard Essential Patents', or 'SEPs', has profound implications for patent owners and implementers. It established that UK courts have the power to settle the terms of global licences for SEPs, and developed the meaning of the non-discrimination component of 'FRAND' (Fair, Reasonable and Non-Discriminatory) terms. However, these appeals leave unanswered a number of related questions – from the proper role of foreign courts to the drafting and practical operation of 'adjustment' clauses – that courts are likely to have to grapple with in future. This article summarizes the issues at stake in the two appeals, examines the arguments in the lower courts and the Supreme Court's reasoning, and looks ahead to the potential impacts of this long-awaited judgment.